2.(3):4/3-13 2/3-(+11+3/4+3/4*1 2/3
Răspunsuri la întrebare
Răspuns de
2
Răspuns:
2.(3):4/3-13 2/3-(+11+3/4+3/4*1 2/3=
21/9×13/4-(13×3+2)/2-[44/4+3/4+
3/4×(1×3+2)/3]=
7/3×13/4-41/4-(47/4+3/4× 5/3)=
91/12-41/4-(47/4+ 5/4)=
91/12- 123/12-52/4=
-32/12-156/12=
-188/12=
-47/3
Explicație pas cu pas:
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă